Thoughts and musings on the development of a theory for rework causation in construction - Love, Peter; Carey, Brad; Sing, Michael; Matthews, Jane (-, 2013)
To learn ‘how’ to mitigate rework, organizations involved in the delivery of construction projects need to be able to make sense and learn from events that lead to its occurrence. The process of retrospective sensemaking can provide an understanding that can inform and direct actions to eliminate rework, which can threaten project performance. In this paper, sensemaking serves as a conceptual foundation to develop a theoretical underpinning for determining the systemic nature of rework. The use of sensemaking can provide an ameliorated understanding of rework causation and enable theory to be developed, as currently no coherent one exists. There is a need for a general set of assumptions, propositions, or accepted facts that attempts to provide a plausible or rational explanation of cause-and-effect relationships for rework. Having a theory in place and subsequently being able to understand ‘how’ and ‘why’ rework arises can provide the feedback required to enable organizational learning to occur and eventually a learning organization.